ANALISIS PENGARUH JASA LAYANAN TERHADAP KEPUASAN NASABAH: Bukti Empiris Pada PT. Bank Aceh Syariah Kota Banda Aceh - AR, Yazid; Musrizal, Musrizal; Hismendi, Hismendi (Jurnal Sains Riset, 2022)
This research is intended to analyze the effect of service on the level of customer satisfaction at PT. Bank Aceh in Banda Aceh City in terms of the dimensions of physical evidence, reliability, responsiveness, assurance and empathy. This study uses primary data for the period 2021. The analytical method used is Ordinary Least Square (OLS). The results showed that the variables of physical evidence, reliability, responsiveness and assurance had a positive effect on customer satisfaction. For that researchers expect the management of PT. Bank Aceh pays attention to customer satisfaction as a response to experiences related to the products or services provided. Emotional responses are stimulated by cognitive evaluative processes in which perceptions (beliefs) of an object, action, or condition are compared with one's values (needs, wants, desires).Keywords:     service, tangible, reliability, responsiveness, assurance and empathy